Impact of 1:1 iPads on teachers and teaching - Caponigri, David (My University, 2014)
This study examined the effects of how 1:1 iPads (1 student to 1 iPad) impacted preparation, delivery and feedback for teachers. In particular, this study investigated delivery, efficiency, student engagement, assessment/feedback, and intervention and how 1:1 iPads allowed for new approaches to lesson delivery that would otherwise be difficult to impossible without 1:1 iPads. This study showed how in the 2013-14 school year in a Midwestern Suburban 7th grade Pre Algebra classroom the teacher graded and analyzed the class's work far faster than previously possible. Once the teacher started to become more efficient, the teacher had an opportunity to update teaching practices to match the needs of the classroom. The teacher prepared for lessons in a way that was not previously possible, including meeting with each student with more frequency and improved accuracy of what students needed help and with what topics. The teacher became so efficient that he was even able to run a hybrid classroom.
Plan B Paper. 2014. Master of Science in Education-Mathematics--University of Wisconsin-River Falls. Teacher Education Department. 32 leaves. Includes bibliographical references (leaves 28-29).
Keywords: Algebra--Study and teaching (Middle school)--Audio-visual aids; iPad (Computer); Educational technology--Evaluation; Computer-assisted instruction--Evaluation